1980
DOI: 10.1136/sti.56.4.210
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory properties of serum from patients with different stages of syphilis

Abstract: SUMMARY The response of lymphocytes from 17 patients with primary, secondary, and tertiary syphilis to phytohaemagglutinin (PHA) and to allogeneic lymphocytes was normal in heterologous serum; however, the responsiveness of cells from some patients with primary and secondary disease was significantly reduced in the presence of autologous serum. As cells from healthy controls invariably responded better to these stimuli in autologous serum, the sera from 81 patients with syphilis were screened for immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The host's immune system actively participates in the relentless pursuit and elimination of T. pallidum, while T. pallidum skillfully employs various mechanisms to evade immune recognition, such as suppression of host cellular immune responses. 34,35 Macrophages are the frontline cells of innate defence and play a crucial role in the process of T. pallidum infection. A previous study has demonstrated that Tp92, the outer membrane protein of T. pallidum, induces the death of human monocytes in the early stages of T. pallidum infection, which helps T. pallidum to escape recognition and elimination by the host innate immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host's immune system actively participates in the relentless pursuit and elimination of T. pallidum, while T. pallidum skillfully employs various mechanisms to evade immune recognition, such as suppression of host cellular immune responses. 34,35 Macrophages are the frontline cells of innate defence and play a crucial role in the process of T. pallidum infection. A previous study has demonstrated that Tp92, the outer membrane protein of T. pallidum, induces the death of human monocytes in the early stages of T. pallidum infection, which helps T. pallidum to escape recognition and elimination by the host innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…During T. pallidum infection, the interplay between the evasion strategies of T. pallidum and the host's innate and adaptive immune responses is a complex and dynamic battle. The host's immune system actively participates in the relentless pursuit and elimination of T. pallidum , while T. pallidum skillfully employs various mechanisms to evade immune recognition, such as suppression of host cellular immune responses 34,35 . Macrophages are the frontline cells of innate defence and play a crucial role in the process of T. pallidum infection.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it is important to stress the pitfalls inherent in interpreting in vitro data and determining the relevance it has, if any, to in vivo biological and clinical events. The presence of serum inhibitors has been used by some investigators (5,22,41,42,51,55) to promote a role for immunosuppression in early syphilis. This hypothesis purportedly explains the persistence of the infecting organisms during latency and the subsequent progression to tertiary disease.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence favoring suppression stems from the diminished in vitro mitogenic stimulation of peripheral blood lymphocytes from patients. This suppression is maximal during the secondary stage and is attributed to one or more serum factors (16,27). Since we found that the limitations of the initial IgG response were overcome just before the secondary stage, it seems unlikely that IgG production is connected to this postulated immune suppression.…”
Section: Si+mentioning
confidence: 99%
“…The slow development of host defense mechanisms on the one hand and the absence of positive results in certain in vivo and in vitro immunological tests (14,16,26,27) on the other could complement each other and led to the hypothesis that the immune system is suppressed during early syphilis. However, it is not clear whether some of these findings are * Corresponding author.…”
mentioning
confidence: 99%